2021
DOI: 10.3390/ph14080783
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Safety Profiles of Sedatives Commonly Used in Clinical Practice: A 10-Year Nationwide Pharmacovigilance Study in Korea

Abstract: This study aims to compare the prevalence and seriousness of adverse events (AEs) among sedatives used in critically ill patients or patients undergoing invasive procedures and to identify factors associated with serious AEs. Retrospective cross-sectional analysis of sedative-related AEs voluntarily reported to the Korea Adverse Event Reporting System from 2008 to 2017 was performed. All AEs were grouped using preferred terms and System Organ Classes per the World Health Organization—Adverse Reaction Terminolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Similar to previous studies, our present study suggested an increased risk of drugrelated fatal events in males, elderly patients, and patients concurrently using multiple medications, which was confirmed in the univariate and subsequent multivariate analysis [28][29][30]. While aging and polypharmacy have been extensively reported in previous studies as major risk factors of serious ADRs [28,29], the increased risk of fatal ADRs in males compared to females could not be clearly explained from the physiological standpoint. However, this difference in the risk of drug-induced fatal events between genders might be accounted for by the different attitudes toward health [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to previous studies, our present study suggested an increased risk of drugrelated fatal events in males, elderly patients, and patients concurrently using multiple medications, which was confirmed in the univariate and subsequent multivariate analysis [28][29][30]. While aging and polypharmacy have been extensively reported in previous studies as major risk factors of serious ADRs [28,29], the increased risk of fatal ADRs in males compared to females could not be clearly explained from the physiological standpoint. However, this difference in the risk of drug-induced fatal events between genders might be accounted for by the different attitudes toward health [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…Automated nationwide prospective registration of endoscopic procedures and outcomes may be the only reliable solution, as already successfully implemented in some countries (21)(22)(23)(24). This also accounts for the registration of anaesthesiology-related AE (25,26). Mandatory nationwide registration, which is currently not at the seams in Belgium, will also allow reliable analysis of high-volume data and subsequent publication.…”
Section: Discussionmentioning
confidence: 99%
“…The association of seriousness of drug-induced nephrotoxicity and causative drugs or drug classes was estimated using disproportionality analysis and was expressed in reporting odds ratios (RORs) with corresponding 95% confidence intervals (CIs) and Mantel–Haenszel adjusted p -values. RORs were estimated for specific offending medications or drug classes with at least three SAE reports [ 31 , 32 ]. Univariate analysis was conducted to identify predictors associated with SAEs and certain types of drug-induced nephrotoxicity, and factors included age, causality, sex, and polypharmacy (concurrent administration of at least 5 daily medications).…”
Section: Methodsmentioning
confidence: 99%